ENTREPRENEURSHIP IN NURSING: AN OPPORTUNITY FOR AUTONOMY AND PROFESSIONAL VISIBILITY - Pinheiro, Loyana Mendes; Machado, Thatyana Borges; Bandeira, Suellen Cavalcante; Machado, Adriano Augusto Pereira (Seven Editora, 2024)
Entrepreneurial nursing is an essential approach to face the challenges of the health sector, promoting innovation in the fields of activity and in health care, consolidating the profession with science, technology and giving personal, professional and financial autonomy. Objective: To discuss entrepreneurship in nursing as an opportunity for autonomy and professional visibility. Methodology: Integrative literature review, which used bibliographic sources in the period from 2019 to 2024. Studies were selected through SciElo, PubMed, Virtual Health Library (VHL), and the Federal Council of Nursing (COFEN). The inclusion criteria adopted were documents available in full, in Portuguese and English, which presented aspects related to the theme in the title or abstract. And exclusion, articles and documents published before the established period, as well as those that did not have relevant content for the topic addressed. Results: From the analysis of the data obtained, ten articles were selected for the elaboration of the research, which allowed the analysis of the existing evidence regarding the types of entrepreneurship, the autonomy of the nurse supported by law and the entrepreneurial entrepreneurship in Nursing. Conclusion: Entrepreneurship in nursing represents a powerful opportunity for professionals in this area to reach new levels of autonomy and recognition. DOI:https://doi.org/10.56238/sevened2024.037-050